Glycogen Rich Clear Cell Carcinoma of Breast - Malla, S.; Shakya, Geeta; Regi, S.; Mudvari, D. S. (Journal of Nepal Health Research Council, 2009)
A 37 years old woman presented with a palpable mass in outer upper quadrant of the right breast. Excision biopsy showed Glycogen rich clear cell carcinoma (GRCCC) based on histological, PAS staining and immunohistochemical staining findings Histologically, most of tumor cells were clear cell type with variable intracytopasmic PAS positivity Immunohistochemically, the tumor was positive for progesterone receptor and vimention and foceally positive for cytokeratin and negative for estrogen receptor and S100. The patient underwent right quadrantectomy with right axillary clearance. This case was in stage IIa (T2N0Mx) and Elston and Ellis histological grade 2(Scores 3+2+1=6). GRCCC is a rare variant of breast carcinoma, with incidence calculated to be 1.4 to 3% and reports indicated a poorer prognosis for patient with GRCCC than those with usual breast cancer. Key words: Breast; Cancer glycogen rich clear cell carcinoma doi: 10.3126/jnhrc.v6i2.2218 Journal of Nepal Health Research Council Vol. 6, No. 2, 2008 Page: 117-119